2018
DOI: 10.1007/s10488-018-0854-1
|View full text |Cite
|
Sign up to set email alerts
|

Furthering Our Understanding of Therapist Knowledge and Attitudinal Measurement in Youth Community Mental Health

Abstract: Examining therapist evidence-based practice (EBP) knowledge seems an important step for supporting successful implementation. Advances in implementation science suggest a distinction between practice specific (i.e., knowing which practices are derived from the evidence base) and EBP process (i.e., integrating research evidence, clinical experience, client characteristics, and monitoring outcomes) knowledge. An examination of how these knowledge types are measured and relate to attitudes appears warranted. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 31 publications
0
11
2
Order By: Relevance
“…EBP attitudes was not correlated with, or predictive of residualized change scores in this study. This finding somewhat disagrees with previous research suggesting that there may be a relationship between therapist knowledge and attitudes (Nakamura et al, 2011;Okamura et al, 2018). However, these results may align with certain findings from Nakamura et al (2011), which found that EBP knowledge accuracy did not significantly relate to attitudes towards EBP.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…EBP attitudes was not correlated with, or predictive of residualized change scores in this study. This finding somewhat disagrees with previous research suggesting that there may be a relationship between therapist knowledge and attitudes (Nakamura et al, 2011;Okamura et al, 2018). However, these results may align with certain findings from Nakamura et al (2011), which found that EBP knowledge accuracy did not significantly relate to attitudes towards EBP.…”
Section: Discussioncontrasting
confidence: 99%
“…However, its utility is constrained to the construct of awareness knowledge, or the ability to merely classify a particular technique as being derived or not derived from the evidence-base. The relationship between awareness knowledge and higher order behaviors like procedural knowledge or competence with techniques remains largely unknown (Okamura et al, 2018;Stumpf et al, 2009). A second assessment strategy centered at the practice element metric level is the PETT-T TPOCS (Nakamura & McLeod, 2011;.…”
Section: Therapist Assessment Strategies At the Practice Element Metric Levelmentioning
confidence: 99%
“…Specifically, attitudes can influence the initial decision to consider EBP, how it is implemented and whether it is sustained beyond the implementation phase [ 24 , 26 28 ]. Demographic factors seem inconsistently related to attitudes toward EBP among mental health care providers [ 21 , 29 – 33 ]: Higher age was associated with more positive attitudes in [ 34 37 ], with less positive ones in [ 38 41 ]; women were reported to show more positive attitudes in [ 34 , 36 38 ], whereas other studies found no sex differences [ 26 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to several implementation strategy theories, e.g. Rogers theory Diffusion of innovations [43] and research within EBP [44], providers must not only have favorable attitudes towards it, they also need to have knowledge about the new technique, before successfully adopted into clinical practice. In a recent study of clinicians training in cognitive behavioral therapy with a strong focus on SA tools, the researchers used the ASA questionnaire to investigate the change in attitudes and use of SA before and after training and found that the clinicians developed a more positive attitude towards psychometric quality and feasibility of SA in clinical practices with training [45].…”
Section: Discussionmentioning
confidence: 99%